Conceptual Integration between General Leadership and Political Leadership in the Electoral Context: A Systematic Review of National and International Research Trends - Alfa Rehan Oktori Rahmadana (Advances In Education Journal, 2025)
This systematic review explores the conceptual intersection between general leadership theories and political leadership practices in electoral contexts. By synthesizing national and international literature from the past two decades, the study examines how leadership concepts such as transformational, transactional, servant, and pragmatic leadership inform political leadership during elections. The findings highlight key themes including the growing relevance of pragmatic leadership in polarized societies, the influence of gender expectations on political leadership, and the role of communication strategies during electoral crises, such as the COVID-19 pandemic. The review concludes that integrating these leadership paradigms enriches theoretical understanding and enhances the practice of political leadership in electoral settings.